2008
DOI: 10.1111/j.1600-6143.2008.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Alloreactive (CD4-Independent) CD8+ T Cells Jeopardize Long-Term Survival of Intrahepatic Islet Allografts

Abstract: Despite success of early islet allograft engraftment and survival in humans, late islet allograft loss has emerged as an important clinical problem. CD8+ T cells that are independent of CD4 + T cell help can damage allograft tissues and are resistant to conventional immunosuppressive therapies. Previous work demonstrates that islet allografts do not primarily initiate rejection by the (CD4-independent) CD8-dependent pathway. This study was performed to determine if activation of alloreactive CD4-independent, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…However, more rapid CD8 + T cell response with increased expression of CD69 matches our findings for CD69 expression on day 3. Furthermore, expression of CD69 on peripheral CD8 + cells after kidney transplantation in vivo correlates closely with acute rejection of allografts, and alloreactive CD8 + T cells are considered responsible for late rejection reactions, resulting in diminished longterm survival …”
Section: Discussionmentioning
confidence: 99%
“…However, more rapid CD8 + T cell response with increased expression of CD69 matches our findings for CD69 expression on day 3. Furthermore, expression of CD69 on peripheral CD8 + cells after kidney transplantation in vivo correlates closely with acute rejection of allografts, and alloreactive CD8 + T cells are considered responsible for late rejection reactions, resulting in diminished longterm survival …”
Section: Discussionmentioning
confidence: 99%
“…For example, we have previously reported that CD4 + T cell depletion of islet transplant recipients (whether transplanted by intraportal or kidney subcapsular route) in the same MHC recipient/donor combination as hepatocyte transplant recipients in the current study results in prolonged allograft survival (>70 days) 51 . These long-term surviving islet allografts remain susceptible to rejection since, adoptive transfer of alloreactive CD4-independent CD8 + T cells (stimulated by hepatocyte transplant) results in rejection 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In our model, allospecific CD8 + cytotoxic T lymphocytes (CTL) effector function is significantly enhanced in magnitude and persistence when primed in the presence of CD4 + T cells. However, our studies utilizing transgenic CD8 + T cells suggest that the enhanced cytotoxic effector activity generated in the presence of CD4 + T cells was not a result of enhanced proliferation, precursor frequency, or CD8 + T cell trafficking to the liver sinusoids (site of cellular transplantation) (17, 18). This led us to investigate the hypothesis that CD8 + T cell cytotoxic effector mechanisms which develop in CD4-replete conditions are fundamentally different, and perhaps more complex, from those which develop in CD4-deficient conditions.…”
Section: Introductionmentioning
confidence: 88%